Upshots of Surface Water Quality on the Incidence of Water-Borne Disease Cases in Communities Along River Ase in Southern Nigeria - Ushurhe, Ochuko; Uzowulu, Olannye Donald; Origho, Thaddeus; Tennyson, Edojarievwen Uvietabore; Chukubuzor, Emetulu Victor (CV. Literasi Indonesia, 2024)
In Southern Nigeria, there is the problem of inadequate access to safe drinking water and the incidence of water-borne diseases that reduce vitality and economic productivity. It is on this premise that the paper assesses the upshots of surface water quality on the wide range of water-borne disease cases in the study area. The study employed an experimental and expost facto research design. A surface water sample from each of the six communities along River Ase was analyzed for physicochemical and bacteriological quality parameters using standard procedures for twelve months. The resulting data were compared to the WHO recommended limits and the suitability of the surface water for residential use was determined using the water quality index. In addition, health records of persons diagnosed and treated for water-borne diseases were collected from limited health record centers in the study communities to determine those impacted by water-borne diseases. Data were analyzed using descriptive statistics and multiple regression statistical techniques to test the posited hypothesis (Ho). The results showed that there is variation in the water quality of the river. The posited hypothesis showed that 51% of the incidence of water-borne diseases was significantly dependent on the quality of water at P > 0.05. Also, the WQI indicated that the water quality fell between bad and medium (42.80 - 58.05), indicating that the water should be treated before consumption. The study, therefore, recommends the testing of the water periodically to safeguard human health.